Immediate Implant Placement in Non-Infected Sockets versus Infected Sockets: a Systematic Review and Meta-Analysis - Aza Saijeva; Gintaras Juodzbalys (Stilus Optimus, 2020)
Objectives: The aim of this systematic review is to compare immediate implant placement in infected extraction sockets with non-infected extraction sockets in terms of implant survival and function. Material and Methods: An electronic search was conducted in PubMed, ScienceDirect, ISI Web of Knowledge and Google Scholar between January 2010 and February 2020. Studies evaluating implant survival rate and main clinical parameters were included for a qualitative and quantitative analysis. Results: In total, nine studies were included and a pool of 2281 sockets were analysed. Compared with the non-infected group, the infected group showed no significant differences in implant survival rates (risk ratio [RR] = 0.99; 95% confidence interval [CI] = 0.98 to 1; P = 0.08). No significant statistical differences were found in marginal bone level (mean difference [MD] = -0.03; 95% CI = -0.1 to 0.04; P = 0.41), marginal gingival level (MD = -0.07; 95% CI = -0.17 to 0.04; P = 0.23), probing depth (MD = 0.06; 95% CI = -0.24 to 0.36; P = 0.7), modified bleeding index (MD = -0.00162196; 95% CI = -0.09 to 0.09; P = 0.97) and slight but significant changes were seen in width of keratinized gingiva (MD = 0.25; 95% CI = -0.3 to 0.8; P = 0.38) between the groups at the latest follow-up. Conclusions: There were no significant difference in implant survival rates, marginal bone level, marginal gingival level, modified bleeding index and probing depth between infected sockets and non-infected sockets. However, slight but significant changes were seen in width of keratinized gingiva favouring the non-infected group.